HUNGARIAN RESEARCH ABOUT THE HISTORY AND CULTURE OF THE PEOPLES OF CENTRAL ASIA AND KAZAKHSTAN (Journal of history, 2024)
Current article will be focused to Hungarian researchers’ study on the history and culture of Central Asia and Kazakhstan. Goals and objectives of the study. The purpose of this article is to analyze the main scientific directions of Hungarian researchers who conducted their scientific investigation in Central Asia and Kazakhstan in various chronological periods, which allows to highlight and to trace the continuity of Hungarian scientist’s generation in the named fields of the region. This study uses interviews and survey methods as one of up-to-date research method to inquire. On the framework a qualitative type of research, a sampling method based on the open-ended questions used on creating the interview points. Results. As the consequence, the generations of Hungarian scientists who conducted research expeditions in Central Asia and Kazakhstan were analyzed; interviews collected from modern Hungarian scientists who are currently managing research in this region; determined their scientific directions, topics and research objectives as well. Conclusion. Dates from this study can be used in the field of historiography, history, Turkology etc.
Keywords: Hungarian researchers; Central Asia; Historiography; History; Turkology; Kazakhstan